Compound release from nanostructured lipid carriers (NLCs). (February 2016) - Dan, Nily
Abstract: Active compounds such as flavors, scents, vitamins or nutraceuticals enhance the quality and nutritional value of foods. Their encapsulation in nanoparticles preserves properties such as appearance, while increasing solubility and bioavailability. Nanostructured lipid carriers (NLC) composed of liquid and solid lipid domains are biocompatible and combine high encapsulation rates with mechanical stability. In this paper we use Monte Carlo simulations to investigate the effects of the solid domain properties on the rate of compound release from NLC. Quite surprisingly, solid impenetrable domains at the particle/solution interface hinder release only when the domain size is much smaller than the nanoparticle size, even if they cover a significant fraction of the interface. The geometry of the solid domains also affects the rate of release, and how the rate dependence on domain size and fraction. Highlights: Simulate compound release from nanostructured lipid carriers. The ratio of surface domain size to nanoparticle size affects the rate of release. Domain geometry, fraction and spacing affect the rate of release.